Biochemical analysis and identification of linear B-cell epitopes from recombinant Sm21.7 antigen from Schistosoma mansoni. (September 2018) - Rezende, Cíntia M.F.; Coitinho, Juliana B.; Costa, Mariana; Silva, Marina Rodrigues; Giusta, Mário; Oliveira-Prado, Roberta; Corrêa-Oliveira, Rodrigo; Nagem, Ronaldo; Goes, Alfredo M.
Highlights: Structural and physico-chemical properties of Sm21.7 are described. Nine peptides are identified as linear B-cell epitopes of Sm21.7 protein. Several epitopes within the DLC-domain are recognized by Sm21.7-immunized mice sera. Implications for the development and use of vaccines based on epitopes of Sm21.7 protein are described. Abstract: Schistosoma mansoni tegument is a dynamic host-interactive layer that is an essential source of parasite antigens and a relevant field for schistosome vaccine research. Sm21.7 is a cytoskeleton antigen found in S. mansoni tegument that engenders protection in experimental challenge infection. Because of its crucial role in the parasite tegument and its promising protective capability, Sm21.7 is an exciting target for the development of therapeutic strategies. The present study describes Sm21.7 structural and biophysical features using circular dichroism spectroscopy and identifies linear B-cell epitopes of Sm21.7 using in-silico methods and immunoassay. The Sm21.7 gene was cloned into the pETDEST42 vector, and the recombinant protein was overexpressed in Escherichia coli DE3. The soluble protein was purified by affinity chromatography followed by ion-exchange chromatography. Purified recombinant Sm21.7 was analyzed by circular dichroism spectroscopy which demonstrated that the rSm21.7 structure was comprised of approximately 38% α-helices and its conformation remains stable at temperatures of up to 60 °C. Prediction of rSm21.7 B-cell epitopes was based on amino acid physicochemical properties. Sixteen peptides corresponding to predicted epitopes were synthesized and immunoreactivity assessed by spot peptide array using pooled rSm21.7-immunized mice sera or patients' sera with different clinical forms of S. mansoni infection. Immunoassays revealed that sera from rSm21.7-immunized mice reacted predominantly with peptides located in the dynein-light chain domain (DLC) at the C-terminal region of rSm21.7. Comparative analysis of the antibody response of acute, intestinal and hepatosplenic patients' sera to the Sm21.7 peptides showed that a differential recognition pattern of Sm21.7-derived peptides by intestinal patients' sera might contribute to down-regulate the immune response in chronic intestinal patients. Together, the results may help the development of S. mansoni vaccine strategies based on the rSm21.7 antigen.